2012
DOI: 10.1080/02681102.2011.630312
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between socio-economic status and physical mobility

Abstract: In emerging economies, the socio-economic status is a key element to evaluate social improvement as it provides an understanding of the population's access to housing, education, health or basic services like water and electricity. The relationship between such indicators and human physical mobility has been researched mostly in areas like access to medical infrastructures and public transportation. However, such studies have been limited in scope mostly due to the lack of large scale human mobility informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 12 publications
(18 reference statements)
0
24
0
Order By: Relevance
“…The most significant features were then used in a variety of machine learning techniques, and shown to achieve up to 80% accuracy when classifying areas according to three classes of SEL. The method developed in [29] was further investigated by Frias-Martinez et al [13,12], who then implemented it in a GUI-based system, designed to reduce the number of census areas that needed to be manually surveyed, by using surveyed data as training labels, and using the model to estimate the remainder [11]. This time, the highest accuracy quoted is 76% for a 3-class problem and 63% for a 6-class problem.…”
Section: Related Workmentioning
confidence: 99%
“…The most significant features were then used in a variety of machine learning techniques, and shown to achieve up to 80% accuracy when classifying areas according to three classes of SEL. The method developed in [29] was further investigated by Frias-Martinez et al [13,12], who then implemented it in a GUI-based system, designed to reduce the number of census areas that needed to be manually surveyed, by using surveyed data as training labels, and using the model to estimate the remainder [11]. This time, the highest accuracy quoted is 76% for a 3-class problem and 63% for a 6-class problem.…”
Section: Related Workmentioning
confidence: 99%
“…Chang et al [40] found that the correlations (i.e., 0.9052) of online activities with the tertiary industry was larger than the secondary industry (i.e., 0.8688); and much larger than the primary industry (i.e., 0.0482). The strong relation between socio-economic status and physical human mobility were also observed [41,42]. In all, some literatures used human activities to successfully estimate economic status and demonstrated the hidden correlations of human activities and economic developments [41,42].…”
Section: Literature Reviewsmentioning
confidence: 95%
“…The strong relation between socio-economic status and physical human mobility were also observed [41,42]. In all, some literatures used human activities to successfully estimate economic status and demonstrated the hidden correlations of human activities and economic developments [41,42].…”
Section: Literature Reviewsmentioning
confidence: 95%
“…Other related works include that of Soto et al [24] and Frias-Martinez et al [12,11], in which machine learning methods are used to predict the socio-economic status of a city's neighbourhoods using CDR data. Individual subscribers' mobile phone data is used as input, as opposed to the aggregated data used in the previously mentioned works, which allows for a richer set of features to be created, potentially leading to better predictive performance, but also raises privacy concerns.…”
Section: Related Workmentioning
confidence: 99%